Nature and bureaucracy : the wildness of managed landscapes - Jenkins, David (Anthropologist) (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"This book questions how bureaucracies conceive of and consequently interact with nature, suggests that our managed public landscapes are neither entirely managed nor entirely wild, and offers several warnings about bureaucracies and bureaucratic mentality. One prominent challenge facing scientists, policymakers, environmental activists, and environmentally concerned citizens is to recognize human influence in the natural world is pervasive and has a long history, and to act accordingly-or to choose not to act. Western-style management of nature, mediated by economic rationality and state bureaucracies, may not be the best strategy to maintain environmental integrity. The question is what kinds of human influence, conceived of in the widest possible sense, will produce ideal environments for future generations? The related question is who gets to choose. The author approaches the problem of analyzing the mutual influence of human and natural systems from two perspectives: as an objective scholar investigating bureaucracies and natural systems from the outside, and over the last decade as an inside practitioner working in various roles in federal land management agencies developing policies and regulations involved in the control of natural systems. This book will be of great interest to students and scholars of natural resource management, policy and politics, and professionals working in environmental management roles as well as policymakers involved in public policy and administration"--
Chapter 1. -- Against efficiency: why we cut trees (and what happens when we do) -- Chapter 2. -- When the well runs dry: aquifers, canals, and the Colorado River system -- Chapter 3. -- Atlantic salmon, endangered species, and the failure of environmental policy -- Chapter 4. -- Count every fish: non-market fishing economies on the Yukon River -- Chapter 5. -- Managing natural resources in Alaska: anthropology bureaucratized -- Chapter 6. -- Traditional bureaucratic knowledge: the order of rules -- Chapter 7. -- Bureaucratic management of wildlife: wolves in the state of Alaska -- Chapter 8. -- Enemy ancestors -- Chapter 9. -- To save the spiritual -- Chapter 10. -- Traditional ecological knowledge -- Chapter 11. -- The dharma of nature.
OCLC-licensed vendor bibliographic record.
Keywords: Natural resources -- Management; Public administration; Bureaucracy; NATURE / General; NATURE / Ecology; NATURE / Environmental Conservation & Protection